Exploring Threats, Defenses, and Privacy-Preserving Techniques in Federated Learning: A Survey - Huang, Ren-Yi; Samaraweera, Dumindu; Chang, J. Morris (Computer (Long Beach, Calif.), 2024)
This article presents a comprehensive survey of both attack and defense mechanisms within the federated learning (FL) landscape. Furthermore, it explores the challenges involved and outlines future directions for the development of a robust and efficient FL solution.